Evaluation of the Cleaning Efficiency of 2 Shape, Hyflex EDM and Pro Taper GOLD Systems Using Digital Image Morphometric Analysis (An in Vitro Study) - Safa S. Alobaidy1 , Biland M.S. Shukri2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Aim of the Study: To measure and compare the cleaning efficiency of 2 Shape, Hyflex EDM and Protaper GOLD rotary systems in removing debris and compare the percentage of remaining debris at three different levels of root canal by using digital image morphometric analysis. Material and Method: Total 60 freshly extracted human maxillary first molar with single straight palatal roots were selected were disinfected in a solution of 1% Thymol for 1 day then the palatal roots were sectioned at a length of 12 mm from the apex and randomly divided into three groups of twenty teeth : Group A: Was prepared by 2 Shape file system (Full rotary technique). Group B: Was prepared by Hyflex EDM file system (Full rotary technique). Group C: Was prepared by Protaper GOLD system (Full rotary technique) . All systems were used according to the manufacture instructions and roots prepared to an apical preparation corresponding to size 40 K-file. Sodium hypochlorite (3%) was used as an irrigant for all groups. Conclusions: 2 Shape system was significantly less effective than Hyflex EDM and Protaper GOLD systems in eliminating debris from root canals at all levels. There were no differences in the cleaning efficiency between Hyflex EDM and Protaper GOLD systems at all levels of root canals.